Formation of covalently bound C4H4+ upon electron-impact ionization of acetylene dimer - Wang, Yingying; Wang, Enliang; Zhou, Jiaqi; Dorn, Alexander; Ren, Xueguang (My University, 2021)
We investigate the formation mechanisms of covalently bound C4H4+ cations from direct ionization of hydrogen bonded dimers of acetylene molecules through fragment ion and electron coincident momentum spectroscopy and quantum chemistry calculations. The measurements of momenta and energies of two outgoing electrons and one ion in triple-coincidence allow us to assign the ionization channels associated with different ionic fragments. The measured binding energy spectra show that the formation of C4H4+ can be attributed to the ionization of the outermost 1πu orbital of acetylene. The kinetic energy distributions of the ionic fragments indicate that the C4H4+ ions originate from direct ionization of acetylene dimers while ions resulting from the fragmentation of larger clusters would obtain significantly larger momenta. The formation of C4H4+ through the evaporation mechanism in larger clusters is not identified in the present experiments. The calculated potential energy curves show a potential well for the electronic ground state of (C2H2)2+, supporting that the ionization of (C2H2)2 dimers can form stable C2H2⋅C2H2+(1πu−1) cations. Further transition state analysis and ab initio molecular dynamics simulations reveal a detailed picture of the formation dynamics. After ionization of (C2H2)2, the system undergoes a significant rearrangement of the structure involving, in particular, C–C bond formation and hydrogen migrations, leading to different C44+ isomers.